Designing Innovative Evaluation Instruments for Elementary Teacher Professional Education: A Learning Condition Theory Approach - Syahrial Syahrial; Asrial Asrial; Husni Sabil; Rahmi Rahmi; Miftahul Zannah Azzahra; Ahmad Mansur Nawahdani (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to develop a valid, reliable, and culturally relevant evaluation instrument for assessing the pedagogical competencies of teacher candidates in the Professional Teacher Education Program (PPG) at the elementary school level, based on the Condition of Learning theory. Methodology: The study employed a quantitative approach with validation by six experts and field testing involving 100 teacher candidates. Data analysis included Cronbach's Alpha for reliability measurement. The instrument design adhered to Condition of Learning principles, integrating cultural relevance and pedagogical evaluation. Main Findings: Validation scores ranged from 4.3 to 5.0 across aspects, with a reliability score of 0.72 (Cronbach's Alpha). Evaluation results showed mean scores of 85.05 for cognitive, 80.07 for affective, and 81.14 for psychomotor competencies, indicating strong preparedness among teacher candidates. Novelty/Originality of this study: This study integrates Condition of Learning principles with cultural elements, creating a comprehensive evaluation instrument that reflects Indonesia's educational context. It provides a significant tool for improving pedagogical assessments and aligns evaluation with local values and national education standards. This research has an impact on the creation of more effective and relevant evaluation instruments, so that it can improve the quality of professional education of elementary school teachers through the application of learning conditions theory.